2019
DOI: 10.1098/rsos.191024
|View full text |Cite
|
Sign up to set email alerts
|

Variation in life-history traits amongDaphniaand its relationship to species-level responses to phosphorus limitation

Abstract: Currently organisms are experiencing changes in their environment at an unprecedented rate. Therefore, the study of the contributions to and responses in traits linked to fitness is crucial, as they have direct consequences on a population's success in persisting under such a change. Daphnia is used as a model organism as the genus contains keystone primary consumers in aquatic food webs. A life-history table experiment (LHTE) using four species of Daphnia was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 56 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…In contrast, association with TP, an indicator of nutrient condition, was opposite among haplotypes. This may be due to the intraspecific variation in traits relating to growth and phosphorus-use efficiency, and physiological responses to nutrient limitation (Hartnett, 2019;Sherman et al, 2017Sherman et al, , 2020, as was found experimentally among JPN1 genotypes living in Japan (Tian et al, 2019).We also analysed the effect of the dipteran Chaoborus, whose larva is a predator of Daphnia and whose abundance indicates the abundance of planktivorous fish, because Chaoborus is also preyed on by fish (Sweetman & Smol, 2006). The directions of the effects of Chaoborus also differed among haplotypes, indicating the possibility that predation by this invertebrate predator (Chaoborus larvae) and planktivorous fish on Daphnia influenced the haplotypes in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, association with TP, an indicator of nutrient condition, was opposite among haplotypes. This may be due to the intraspecific variation in traits relating to growth and phosphorus-use efficiency, and physiological responses to nutrient limitation (Hartnett, 2019;Sherman et al, 2017Sherman et al, , 2020, as was found experimentally among JPN1 genotypes living in Japan (Tian et al, 2019).We also analysed the effect of the dipteran Chaoborus, whose larva is a predator of Daphnia and whose abundance indicates the abundance of planktivorous fish, because Chaoborus is also preyed on by fish (Sweetman & Smol, 2006). The directions of the effects of Chaoborus also differed among haplotypes, indicating the possibility that predation by this invertebrate predator (Chaoborus larvae) and planktivorous fish on Daphnia influenced the haplotypes in different ways.…”
Section: Discussionmentioning
confidence: 99%